Multi-arrays of 3D cylindrical microdetectors for beam characterization and microdosimetry in proton therapy - Bachiller-Perea, Diana; Zhang, Mingming; Fleta, Celeste; Quirion, David; Bassignana, Daniela; Gómez, Faustino; Guardiola, Consuelo (Frontiers in Physics, 2022)
The present work shows the performance of two new large microdosimetry multi-array systems having two different configurations, namely, pixel and strip configurations. They cover radiation sensitive areas of 1.9 cm × 0.1 cm and 5.1 cm × 0.1 cm, respectively. The microdosimetry systems are based on arrays of 3D cylindrical silicon microdetectors. The 3D electrodes are etched inside the silicon and have a 25 μm diameter and a 20 μm depth. Each of these unit cells is completely isolated from the others and has a well defined 3D micrometric radiation sensitive volume. The pixel-type device consists of four arrays of 25 × 5 independent silicon-based detectors (500 detectors in total), each one connected to a readout channel, collecting information in 2D in the transverse plane to the particle beam direction. The distance between the individual detectors (pitch) is 200 μm in the horizontal axis and 250 μm in the vertical one. In the case of the strip-type system, we have 512 "columns" (or strips) of 10 detectors per column. Each column is connected to a readout channel, giving us information in one dimension, but with better statistics than a single pixel. In this system, both the horizontal and vertical pitches are 100 μm. Both systems have been tested under proton beam irradiations at different energies between 6 MeV and 24 MeV to obtain the corresponding microdosimetry quantities along the Bragg peak and distal edge. The measurements were performed at the Accélérateur Linéaire et Tandem à Orsay (ALTO, France). The microdosimetry quantities were successfully obtained with spatial resolutions of 100-250 μm. Experimental results were compared to Monte Carlo simulations and an overall good agreement was found. Both microdetector systems showed a good microdosimetry performance under clinical-equivalent fluence rates along distances of several centimeters. This work demonstrates that the two new systems having different configurations can be clinically used as microdosimeters for measuring the lineal energy distributions in the context of proton therapy treatments. Additionally, they could be also used for beam monitoring.